(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The researchers proposed a system entitled automated library management system for Llano High School to manage and monitor the books in the library. The library management system is designed to help the admin maintain and organize the library. Using this system, the librarian can easily monitor the borrowed/returned books. Unauthorized people cannot easily access the system. The researchers used the systems development life cycle process to complete this project. In the planning stage, the researchers planned to make a system for Llano High School. In the analysis stage, the researchers analyzed the idea and data that the client gave us. In the design stage, the researchers designed the system using ERD, flowchart, and use case. In the development stage, the researchers built the system by using coding. In the testing stage, the researchers tested the system after developing it before they gave it to their client. In the implementation stage, the researchers made a printed user manual and will set a one-on-one seminar to instruct the user. In the maintenance stage, the researchers updated the system if necessary. The researchers developed the following deliverables: registration form, to create a new account for the new admin; login form, they must enter the account to enter to the system. This system has a maximum login attempt for the security of the system; after three attempts, the system will not let anyone type or click any button in the system. In student and book management, the user can add, delete, edit, and update book records. They can also create backups for emergency purposes. Restore backup is for the admin to retrieve the backed-up data easily. The search engine allows the admin to search quickly and easily. They can print a report to inform the teachers which students have not to return the book they borrowed yet. All reports will contain information such as book titles and several borrowed books. The proposed system is an automated library management system. Through the researchers’ system, the admin can add members, add books, search books, and update information if some students borrowed or returned the books easily. Having a library management system in a library will make the flow more efficient. However, the client has no Wi-Fi connection; hence, they cannot monitor the borrowed/returned books well.